New Paradigm for Local Financial Management: A Review of Local Budgeting System - Karianga, Hendra (Hasanuddin University, 2016)
Fiscal decentralization gives authority to the head of region and regional parliament to manage the local budget. The outcomes of the research indicate that the Good Financial Governance principle has been subject to frequent study in its understanding as a new paradigm for local financial management. As it turns out in practice, however, it has certain weaknesses, particularly in view of the accountability and legitimacy aspects of its establishment. In fact, the local budget has become a vehicle for corruption by the state administration is in the center of power, local autonomy shift some corruptor from the center to the local. The issue is how to manage the local budget in order to minimize corruption. If the commitment of the management of local budget is based on new principles in the local financial management, it believed that the local budget is governed annually by the local government will lead to the peopleâs welfare in the region. Based on such view, the Good Financial Governance principles appears to be the ideal approach to be applied in managing the local budgeting system.